2012
DOI: 10.1002/jnr.22799
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of ryanodine receptors in tetanic sciatic stimulation‐induced long‐term potentiation of spinal dorsal horn and persistent pain in rats

Abstract: Tetanic stimulation of the sciatic nerve induces long-term potentiation (LTP) of C-fiber-evoked field potentials in the spinal dorsal horn and persistent pain, suggesting that spinal LTP may be a substrate for central sensitization of the pain pathway. However, its cellular mechanism remains unclear. The present study provides electrophysiological and behavioral evidence for the involvement of ryanodine receptor (RyR) in the induction of spinal LTP and persistent pain in rats. The specific inhibitor of ryanodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Increasing evidence has shown that the synaptic plasticity of dorsal horn neurons contributes to pain hypersensitivity after noxious stimulation 15 16 . Additionally, noxious stimulation of the sciatic nerve induces long-term potentiation of C-fiber-evoked field potentials in the spinal dorsal horn and leads to persistent pain 17 . Several intracellular signaling pathway and protein kinase cascades mediate the formation of synaptic plasticity of dorsal horn neurons after noxious stimulation 18 .…”
mentioning
confidence: 99%
“…Increasing evidence has shown that the synaptic plasticity of dorsal horn neurons contributes to pain hypersensitivity after noxious stimulation 15 16 . Additionally, noxious stimulation of the sciatic nerve induces long-term potentiation of C-fiber-evoked field potentials in the spinal dorsal horn and leads to persistent pain 17 . Several intracellular signaling pathway and protein kinase cascades mediate the formation of synaptic plasticity of dorsal horn neurons after noxious stimulation 18 .…”
mentioning
confidence: 99%
“…Previous reports have shown that neuronal cell stimulation promotes Ca 2+ entry mediated by voltage or agonist-activated plasma membrane Ca 2+ channels; through CICR the resulting cytoplasmic Ca 2+ signals stimulate Ca 2+ release from the ER, amplifying the initial signal and triggering neuronal responses necessary for processes involved in memory and learning (Balschun, 1999 ; Shimuta et al, 2001 ; Galione and Churchill, 2002 ; Mellentin et al, 2007 ; Galeotti et al, 2008 ; Adasme et al, 2011 ; Baker et al, 2011 ; Lü et al, 2012 ; Hopp et al, 2014 ). Here, we report that spatial memory consolidation produced a significant increase in RyR2 mRNA and protein contents when tested 3 days after the end of training; these levels were increased even after 10 or 19 days after training, albeit at these later times the RyR2 increments did not reach significance.…”
Section: Discussionmentioning
confidence: 99%
“…Ryanodine receptors (RYRs) main agonist is Ca 2+ itself and they play an important role in the amplification of presynaptic Ca 2+ signals leading to neurotransmitters release [112,113] and have been proposed to participate in pain chronicity both in nociceptive neurons via stimulation of calcium-/CaM-dependent protein kinase CaMKII [114] and in the spinal cord dorsal horn triggering the induction of long-term potentiation at C-fibre synapses [115][116][117].…”
Section: Endoplasmic Reticulum Calcium Releasementioning
confidence: 99%